Legal Protection for Taxpayers in Filing Objections to Land and Building Tax: Perlindungan Hukum Bagi Wajib Pajak dalam Pengajuan Keberatan Pajak Bumi dan Bangunan - Budi Putra Cesariyanto (Universitas Negeri Semarang, 2012)
Legal protection in the field of taxation is a form of protection of the rights and obligations of taxpayers are protected by the Act in order to obtain a legal certainty, so that it can be fought. This study aims to determine the Protection of the Law given to taxpayers in the filing of the objection land and building tax in the East Semarang Primary KPP. These results indicate that the legal protection sought by the KPP Primary East Semarang and ranks top tax official is not maximized. As a recommendation to the forum or container formed East Semarang Primary KPP to coordinate on each sub-villages in the region of East Semarang Primary KPP, to accommodate the grievances suffered by the United Nations Taxpayers can actually be used as the socialization of rules on objections.